Active suspension structure for micro-scale probing systems - Alblalaihid, Khalid (2016)
The continued trends of product miniaturisation and increased part complexity have led to a requirement for highly accurate coordinate metrology, suitable for small parts. Coordinate metrology of such parts is performed on a micro-coordinate measurement machine (micro-CMMs), for which a specialised micro-scale probing system is required. These probing systems consist of a probe onto which a stylus is mounted. The probe provides significant flexibility allowing the stylus tip to be easily deflected during contact with a surface. Achieving an optimum stiffness for the probe represents a significant design challenge, and often leads to undesirable compromises. For example, as stylus tip size reduces the contact pressure for a given load increases, requiring the probe stiffness to be kept as low as possible to prevent damage to the part surface; however, for a more robust probing system the stiffness should be increased. This thesis presents an improved tactile micro-probing system that makes use of an active suspension structure that can be tuned to have either low or high stiffness as required for each phase of a measurement. Development of the probe includes analytical and numerical modelling for a range of solutions as well as empirical investigations into the manufacture of a smart suspension structure for a prototype probing system. Modelling results demonstrate significant stiffness reduction is possible by using the concept of adjusting the internal strain of suspension beam elements. In principle stiffness may be reduced down to zero at the point of beam buckling. It is also shown that such a probing system can provide isotropic stiffness for a range of different styli lengths. A prototype of the suspension structure was fabricated using a chemical etching process and 6.6 mm long stylus. The stiffness of the structure was assessed by measuring the modal frequencies of the suspension structure that correspond to vertical and lateral probe motion. Using this method, results show it is possible to reduce the frequency of the vertical mode and the torsional mode by 70 % and 33 %, respectively. Using finite element analysis it is shown that this equates to a reduction in vertical and lateral stiffness to 12 % and 46 % of their initial value, respectively, representing a ratio of the vertical to lateral stiffness of 1.7, which is close to the isotropic stiffness. A novel control system is presented that monitors and controls stiffness, allowing easy switching between “stiff” and “flexible” modes. During switching, the stylus tip undergoes a displacement or approximately 18 μm, however, the control system is able ensure a consistent flexible mode tip deflection to within 12 nm in the vertical axis. Combining stage errors with the probing system linearity error, the stylus tip zero offset position error and the probing system measurement repeatability, gives an estimate of a combined uncertainty for the probing system or of 58 nm (coverage factor, k = 2), which demonstrates the potential of this innovative variable stiffness micro-scale probe system.